(untitled) (International Seven Journal of Health Research, 2023)
Chronic pancreatitis is a syndrome with several conditions, resulting in similar phenotypic manifestations. Pancreatic biopsy would be the gold standard for diagnosis, but it is often not possible to perform. If chronic pancreatitis is suspected, early diagnosis facilitates appropriate management and prevents complications. In this context, secretin-induced magnetic resonance cholangiopancreatography (s-CPRM) is one of the tests used. This study aims to determine the accuracy and efficiency of s-CPRM in the early diagnosis of chronic pancreatitis, comparing its results with those of other methods used for this purpose, as well as analyzing its cost-benefit ratio. A systematic review was carried out in accordance with PRISMA recommendations. The data from each article used was summarized in a table with the following topics: DOI; first author; year; location; type of study; target population; importance of s-CPRM; other methods and conclusions. We included articles with adults over the age of 18; in English or Spanish; talking about s-CPRM; studies from 2018 onwards; articles comparing the techniques researched. Case reports, editorials and editor’s opinions, and animal studies were excluded. Articles from previous years were added to expand the scarce literature. s-CPRM is a low-invasive test that analyzes pancreatic structure and function, presenting diagnostic results that are comparable and even superior to those of other methods. It faces difficult access to specialized professionals, in addition to the high costs of equipment and secretin. However, as early diagnosis can contain the progression of the disease, avoiding future treatment costs, investing in this test is valid and necessary.